2022
DOI: 10.3390/wevj13120229
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Vehicle Mechatronic Inertial Suspension, Employing a Bridge Electrical Network

Abstract: Inerters, a new type of mass element, have been successfully applied in various fields, such as in automotive and civil engineering. The development of a new element, named a mechatronic inerter, which consists of a ball-screw inerter and permanent magnet electric machinery, proves the feasibility of adopting electrical element impedances to simulate corresponding mechanical elements. In this paper, the structures of the bridge electrical network and series-parallel electrical network and their impedance chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The selection and solution of the impedance transfer function T(s) in the model determines the performance of the suspension. The existing research results show that the higher the order of the impedance transfer function, the better the vibration damping performance [44]. However, considering the complexity of the optimization solution, only T(s) is considered as the biquadratic impedance transfer function, where the expression of biquadratic impedance transfer function is shown in Formula (6):…”
Section: Modeling Of Vehicle Seat Isd Suspensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection and solution of the impedance transfer function T(s) in the model determines the performance of the suspension. The existing research results show that the higher the order of the impedance transfer function, the better the vibration damping performance [44]. However, considering the complexity of the optimization solution, only T(s) is considered as the biquadratic impedance transfer function, where the expression of biquadratic impedance transfer function is shown in Formula (6):…”
Section: Modeling Of Vehicle Seat Isd Suspensionmentioning
confidence: 99%
“…In order to further study the impact of mechatronic inerter on the vibration isolation performance of ISD suspension, Shen et al [43] proposed a mechatronic ISD suspension system optimization design method based on fractional-order electrical ne twork. Zhang et al [44] used the bridge network structure as the outside electrical network of the mechatronic inerter to effectively improve the ride comfort of the vehicle. All the above studies have shown that mechatronic ISD suspension can greatly enhance the vibration isolation performance of the suspension system.…”
Section: Introductionmentioning
confidence: 99%
“…An offline optimization and online fine-tuning method for fuzzy neural network parameters were proposed using a particle swarm optimization algorithm and gradient descent method. Reference [4] focuses on developing a mechatronic inerter consisting of a ball-screw inerter and permanent magnet electric machinery. The study proves the feasibility of using electrical element impedances to simulate corresponding mechanical elements.…”
Section: Suspension Systemmentioning
confidence: 99%